A preliminary study into the sensitivity of disease activity detection by serial weekly magnetic resonance imaging in multiple sclerosis. Issue 3 (March 1996) - Lai, M; Hodgson, T; Gawne-Cain, M; Webb, S; MacManus, D; McDonald, W I; Thompson, A J; Miller, D H
Abstract : Long TR and gadolinium enhanced spin echo brain MRI was performed weekly for three months in three patients with relapsing-remitting or secondary progressive multiple sclerosis. During the study, 38 new enhancing lesions were seen; 11 showed enhancement for less than four weeks, and two enhanced on only one scan. All 16 new lesions seen on long TR scans showed initial enhancement. When only every fourth (monthly) scan was analysed, a total of 33 new enhancing lesions were seen. Subject to confirmation in a larger cohort, the results suggest: (a) that blood brain barrier leakage is an invariable event in new lesion development in relapsing-remitting and secondary progressive multiple sclerosis; (b) the small increase in sensitivity of weekly scanning does not justify its use in preference to monthly scanning when monitoring treatments.